Endothelial Nogo-B regulates sphingolipid biosynthesis to promote pathological cardiac hypertrophy during chronic pressure overload - Zhang, Yi; Huang, Yan; Cantalupo, Anna; Azevedo, Paula S. [UNESP]; Siragusa, Mauro; Bielawski, Jacek; Giordano, Frank J.; Di Lorenzo, Annarita (Amer Soc Clinical Investigation Inc, 2016)
We recently discovered that endothelial Nogo-B, a membrane protein of the ER, regulates vascular function by inhibiting the rate-limiting enzyme, serine palmitoyltransferase (SPT), in de novo sphingolipid biosynthesis. Here, we show that endothelium-derived sphingolipids, particularly sphingosine-1-phosphate (S1P), protect the heart from inflammation, fibrosis, and dysfunction following pressure overload and that Nogo-B regulates this paracrine process. SPT activity is upregulated in banded hearts in vivo as well as in TNF-alpha-activated endothelium in vitro, and loss of Nogo removes the brake on SPT, increasing local S1P production. Hence, mice lacking Nogo-B, systemically or specifically in the endothelium, are resistant to the onset of pathological cardiac hypertrophy. Furthermore, pharmacological inhibition of SPT with myriocin restores permeability, inflammation, and heart dysfunction in Nogo-A/B-deficient mice to WT levels, whereas SEW2871, an S1P 1 receptor agonist, prevents myocardial permeability, inflammation, and dysfunction in WT banded mice. Our study identifies a critical role of endothelial sphingolipid biosynthesis and its regulation by Nogo-B in the development of pathological cardiac hypertrophy and proposes a potential therapeutic target for the attenuation or reversal of this clinical condition.